Take the 2-minute tour ×
Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

I need help to determine $x$ and $y$ intercepts for $$ y = 4(x - 2)^2(x + 2)^3 $$

I guess my first question is, do I need to get the equation into $$ ax^3 + bx^2 + cx + d $$ form before starting?

share|improve this question
    
Would I then just use the x - 2 and x + 2 to determine that the x-intercepts are at 2 and -2? When I graph it, that shows that would be correct. –  erimar77 Nov 8 '11 at 21:35
    
In general, the more "structure" an expression has, the easier it is to solve problems about it. Multiplying out tends to destroy structure. –  André Nicolas Nov 8 '11 at 21:36
add comment

5 Answers

up vote 2 down vote accepted

The $x$-intercepts are defined to be the points where $y=0$. Since what you have is factored, it is easy to see where $y=0$. If $y=0$ then one of the factors must be $0$. The $y$-intercept is where $x=0$. If it exists, it is unique. Just plug in $x=0$ and see what you get.

share|improve this answer
    
Would I then just use the x - 2 and x + 2 to determine that the x-intercepts are at 2 and -2? –  erimar77 Nov 8 '11 at 20:48
    
@erimar77: Yes. –  Joe Johnson 126 Nov 8 '11 at 22:40
add comment

That would be counterproductive.

The $x$-intercepts are solutions to $y=0$, and your equation is set up so that this is easy to solve.

For the $y$-intercept, just set $x=0$ and calculate $y$.

share|improve this answer
add comment

Multiplying is easy; factoring is hard. (Believe it or not, that's why it's hard for identity thieves to steal your money in properly secured e-commerce transactions. Unless maybe the thief is the Prince of Mongolia and you're inexperienced.)

If you had a polynomial in the form $ax^3 + bx^2 + cx +d$, you'd have to factor it to find the $x$-intercepts. This one you've already got in factored form.

share|improve this answer
add comment

The x-intercepts can be calculated like this:

$$ y = 4(x - 2)^2(x + 2)^3 $$ $$ y = 0$$

$$ a \cdot b \cdot c = 0 \rightarrow a = 0 \vee b=0 \vee c=0 $$

$$ 4 = 0 \vee (x-2)^2 = 0 \vee (x+2)^3 = 0$$

$$ None \vee x = 2 \vee x \ -2$$

The y-intercept can be found by substituting $0$ for $x$ in $4(x - 2)^2(x + 2)^3$.

share|improve this answer
add comment

The zeroes of the equation $y = 4(x-2)^2(x+2)^3$ are clearly defined as $x = +2, -2$ which everyone stated. Another idea which I think is interesting is the equations behaviour around these roots. The factor $(x-2)^2$ has an order of $2$ therefore near this root the equation will "bounce" or act quadratically. The factor $(x+2)^3$ has an order of 3 therefore the equation will act cubically near this point, with an inflection at the root.

share|improve this answer
add comment

Your Answer

 
discard

By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.